Le Havre : de ville reconstruite à patrimoine moderne - Jéssica Gomes da Silva; Ana Elisabete de Almeida Medeiros (Confins)
The French city of Le Havre, today a World Heritage Site recognized by Unesco in 2005, had its urban center practically rebuilt after the bombings of World War II. The long process that separates these two dates, from 1944, the year of destruction, until 2005, the date of recognition, was marked by countless actions, discussions and agents that involved its patrimonialization. This article addresses that path, shedding light on Le Havre from the past, which was rebuilt to the city listed on Unesco, keeping the focus on the field of heritage and preservation.